Sustainability and Workforce Development in Maine - Renault, Catherine; Silka, Linda; Ward, James (Maine Policy Review, 2012)
Maine is facing challenges in terms of its workforce: education levels lag behind those in the other New England states; population growth is slow; and the economy is undergoing a change that has shifted from manufacturing to more knowledge-based jobs. Catherine Renault, Linda Silka and Jake Ward discuss these challenges, looking at what employers want in their employees and at the kinds of jobs the state is likely to see in the future. They point out that the Sustainability Solutions Initiative, with its emphasis on a boundary-crossing approach to education, is an example of a way to train today’s students to fill and create the jobs of the future.
Keywords: Maine; sustainability; work force development